Natural Decay Resistance of Indian Timbers I. Introduction and Method, II. Decay Resistance of Sal (Shorea robusta Gaertn.) and Teak (Tectona grandis L.f) - Bakshi, B. K.; puri, Y. N.; Singh, Sujan (Indian Forester, 1967)
Soil-block method for evaluation of natural decay resistance of timber under laboratory conditions is described in detail. Timbers are proposed to be classified into four decay resistance classes based on weight loss per cent in the blocks tested. This classification is based on the weight loss ranges as given in the U.S. Standard: ASTM: Designation: D2017-63, viz. 0-10% (very resistant), 11-24% (resistant), 25-44% (moderately resistant), and 45% and above (non-resistant), with the modification that each class is further divided into 3 sub-c1asses, to distinguish species within the main classes. Decay resistance of heartwood from 21 samples of sal ond 23 samples of teak, both from outer and the inner heartwood regions at the same radius, is tested. Sal heartwood, from outer zones, at the same radius is generally ’very resistant’ (Av. Weight loss 0.20-4.19%). Some tendency towards a lesser decay resistance in the inner heartwood zone in quality class I & II sa1 is evident (weight loss 0.24-21.06%). No such difference, however, is evident in Sal trees of quality class III (weight loss 0.10-4,12%). Also, no difference in decay resistance with respect to vertical position of heartwood in the 3 trees of quality class III was noticed. Teak outer heartwood varies in decay resistance from very resistant to ’moderately resistant’ (weight loss 1.98-25.63%). In older trees (age or heartwood 54-97 based on ring counts) inner heartwood is less resistant than ’outer’ heartwood within the same sample. In younger trees (age of heartwood 11.47 hased on ring count.), entire heartwood of a sample is generally of the same resistance class and compares with inner heartwood of older trees. Variations in decay resistance appear to be correlated with age of trees, rate of growth and radial position of heartwood in the logs.